’n Groene in De Nieuwe Gids, Frederik van Eeden, De kleine Johannes en die ekologisme - W. van Zyl (Literator, 1995)
An ecologist in De Nieuwe Gids, Frederik van Eeden’s De kleine Johannes and ecologism The famous late nineteenth-century Dutch literary rebels, the Tachtigers, chose a part of Frederik van Eeden's De kleine Johannes as the opening text for the first edition of their literary mouthpiece, De Nieuwe Gids. Closer analysis in this article shows, however, that the novel contradicts precisely those literary ideals it was supposed to embody. Much more than being an illustration of the Romantic poetics favoured by the movement, it tends to be a rather didactic defence of ecological ideals and a literary preview of ideas Van Eeden would later advocate much more outspokenly. In his so-called Walden Experiment, inspired by the views of the American ecologist Henry David Thoreau, he would even try to put these ideals into practice. This experiment did not bring about the social success Van Eeden hoped for, but in an ironical way it did fulfil a prophecy in De kleine Johannes: “Among people you will experience endless sorrow…”.